(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
The study is directed to the issue of identification of how the branding strategies of the Nigerian Bottling Company (NBC) are used to change consumer attitudes towards the country’s blue economy. The objective here is to look into aspects that make consumers choose NBC’s eco-friendly brand and indicate useful approaches to green branding. Through in-depth discussions with the marketing and sustainability experts of NBC, we can obtain insights into the company’s initiatives. The consumer survey will monitor the audience’s level of awareness, attitudes, and purchase intentions. The revealed results of the qualitative and quantitative studies are to pinpoint the most significant factors that promote sustainable brand image among Nigerian consumers. This study expands existing knowledge on sustainable branding in Nigeria’s blue economy, adding to literature that is still quite limited by illustrating how consumption behavior impacts branding dynamics and brand maintenance approaches in this environment. The above findings will apply to NBC as well as other operators in the ocean industry. Eco-conscious consumers will be attracted if these companies operate sustainably according to the principles of environmentally friendly branding.